The Effects of Nitrogen and Oxygen Atmosphere on the Photoconductivity of Trimethyl Phenyl Diamine Thin Films - Nazrul Anuar Nayan; Khairul Anuar A. Rahman (Institute of Advanced Engineering and Science, 2018)
Organic materials were previously used as insulators in electrical technology. These materials, however, are currently used as conductors once their photoconductivity is confirmed and studied. From the literature, it has shown that the photoconductivity of trimethyl phenyl diamine (TPD) increases in the air and decreased in the atmosphere of the vacuum. To the best of our knowledge, there is no detailed study of the effects of gas in the air that affect TPD photoconductivity. In this study we investigate the effects of nitrogen (N2) and oxygen (O2) gases on photoconductivity, degradation and residual decay of photoconductivity for thin film TPD. The results of the study show that in the atmosphere of O2, TPD produces about seven times higher photoconductivity compared to N2 conditions. It also shows that, N2 and O2 provide more effective response time during photoconductivity residual decay. Photoconductivity degradation occurs in all conditions and its recovery takes more than 65 hours.